Synthesis and Structural Characterization of some 3-oxapentane Podand Derivatives - Manh Linh, Nguyen; Tam, Pham Thi Thanh; Thuyen, Do Thao; Dat, Nguyen Tien; Van, Tran Thi Thanh; Huyen, Nguyen Thi Thanh; Nhung, Dao Thi; Duan, Le The; Anh, Le Tuan (VNU Journal of Science: Natural Sciences and Technology, 2023)
A series of eight 3-oxapentane podand derivatives was successfully prepared  based on the croton condensation reaction from 1,5- bis (aryl)-1,5-dithia-3-dioxadecane and 1,5- bis (aryl)-1,3,5-trioxadecane with bezaldehyde or acetophenone derivatives in acidic condition. These synthesized derivatives have structure of acyclic crown rings inserted by polyether or polythiaether chain and vinyl ketone chain conjugated with aryl group. Therefore, they are important sources for host-guest chemistry. They can wrap around a central alkali metal cations as well as organic cations and anions or even molecules to make interesting ion pair receptors. Structure of new podands was determined by spectral analyses including IR, 1 H NMR, MS spectrocopies.